Religion and the Environment - Tanner, R. author. aut Link
X, 246 p.
Keywords: This book is an analysis of the whole frontier between religion and the environment. It deals in turn with their interactions and the effects of each on the other in the major world religions. It considers the religious impact on human uses of time, space, materials, transport, and foods, and the environmental effects of religious influence on major topics such as population pressures, morbidity, mortality, marital arrangements, contraception, the treatment of animals, and environmental management.